Behavior of Career Women in Exclusive Breastfeeding to Fulfill Baby Nutrition (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
Breastfeeding is a realization of nature task and precious duty of a mother. Not all mothers are able to pass this task well, one of them is a career woman. The purpose of the study was to analyze the behavior of exclusive breastfeeding application among career women. The research is qualitative with a phenomenological approach. The informants were 3 breastfeeding mothers in the Pesurungan Lor village, Tegal district, Central Java province. The results of informants interviews will be obtained information about various perceptions, feelings, breastfeeding motivation, mothers knowledge and understanding, and the implementation of exclusive breastfeeding, obstacles and support during work. This information can be used as a reference for researchers in providing breastfeeding counseling to career women from pregnancy to postpartum. For the government, it could be used as an evaluation of the success of the exclusive breastfeeding program so as to contribute in increasing the coverage of exclusive breastfeeding for infants, to achieve optimal growth and health.